FACTORS AFFECTING IMPULSE BUYING IN ALFAMART CUSTOMERS IN UJUNGBERUNG SUB-DISTRICT, BANDUNG - Aryani, Rita; Arifianti, Ria; ., Suryanto; Purnomo, Margo (Advances in Social Sciences Research Journal, 2018)
Consumer behavior that draws in the behavior of the modern retail is impulse buying or commonly known as marketers with unplanned purchase. Impulse buying is part of a condition called unplanned buying or an unplanned purchase that is more or less happened to be different with the consumer’s spending plan. Type of the research is field research. This study uses the data obtained from field studies by ways of observing, recording and collecting various information and data found in the field through case studies and surveys. Based on the research, the most dominant factor affecting impulse buying is spontaneous decision factor. Based on the results of descriptive statistics, spontaneous decision factor is characterized by a feeling of excitement and feeling of spirit.